Rural, Pregnant, and Opioid Dependent: A Systematic Review - Naana Afua Jumah (SAGE Publishing, 2016)
The nature, impact, and treatment of substance use during pregnancy are well described for women living in urban settings. Less is known about pregnant substance-using women living in rural communities. The objective of this review is to describe the existing evidence for the management of substance use in pregnant women living in rural areas. A systematic review of the literature was conducted using PubMed, Embase, and the Cochrane Database of Systematic Reviews, and the quality of the evidence was assessed using the GRADE system. Twenty-two articles that met the inclusion criteria were identified. Descriptive studies document high rates of smoking, marijuana, and polysubstance use among rural, substance-using pregnant women compared to their urban counterparts. Management of substance use disorders is limited by access to and acceptability of treatment modalities. Several innovative, integrated addiction and prenatal care programs have been developed, which may serve as models for management of substance use during pregnancy in rural settings.